PRACTICE APPROACH TO THE DESIGN OF POSYANDU SIRNAGALIH VILLAGE, TAMANSARI DISTRICT, BOGOR - Rita Laksmitasari Rahayu; Ukti Lutvaidah; Lukman Afif (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
Posyandu RT 01/11 Sirnagalih Village, Tamansari District, Bogor Regency, is at the foot of Mount Salak. Posyandu is planned to be built on an area of 225 m2. Location temperature conditions range from 180 C in the rainy season to 250 C in the dry season. The sanitation conditions of the houses in this village are not good, so that children and the elderly in Sirnagalih Village are susceptible to disease. Cold weather conditions and high humidity. The average temperature at the location is 200C to 240C, even at certain times the temperature can reach 180C. The humidity in the house in Sirnagalih village is 90.9% in bad condition. As a public health implementation facility, the presence of posyandu is very important, especially to support the government's goal of creating healthy and superior communities. There are 5 main activities, namely: Mother and Child Health (MCH), Family Planning (KB), immunization, nutrition, and diarrhea management. The main activities can be added according to community agreement to become "Integrated Posyandu". One of the current issues is reducing the stunting rate, given the high stunting rate. The problem of stunting has become a world problem since 10 years ago. The purpose of the existence of Posyandu is always in an effort to help the community from not knowing to being able to carry out the introduced behavior or aspects of action or practice. Starting from not knowing to knowing (knowledge), from knowing to wanting (attitude), and from wanting to become practice. The theme of the Posyandu design cannot be separated from the purpose of the Posyandu as the design theme. For this reason, the design approach uses the concept of building reliability which pays attention to safety, health, comfort and convenience.